PENGARUH PENYULUHAN TABLET FE TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG TABLET FE DI DESA NGEMPLAK KECAMATAN GEBANG KABUPATEN PURWOREJO - Zuliyanti, Nurma; Hidayati, Ulfah; Rofingatul Karomah, Miftahu; Arviyani, Ria; Mulyani, Sri (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2024)
ABSTRACT Based on a preliminary study conducted in Ngemplak Village, Gebang District, Purworejo Regency, data was obtained for 21 young women, 16 young women did not know about Fe tablets and 5 young women already knew about Fe tablets. The aim of this research was to determine the effect of FE tablet counseling on young women's knowledge about FE tablets in Ngemplak Village, Gebang District, Purworejo Regency. This type of research is a pre-experimental design with a One Group Pretest-Posttest Design. The population in this research was 50 young women. Determining the number of samples using the Slovin formula obtained a sample of 21. The sampling technique used purposive sampling. The research time was September 6 - September 17 2023. Data analysis used the Paired t test. Where the results show that there is an influence if (p>0.05) for the counseling variable (p value: 0.000), knowledge (t: -8.919). Keywords: Counseling, Knowledge, Fe Tablets